2023
DOI: 10.1089/3dp.2021.0235
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Noncytotoxic High-Resolution Microchannels in Bisphenol-A Ethoxylate Dimethacrylate Tissue-Mimicking Materials

Abstract: The ability to create cell-laden fluidic models that mimic the geometries and physical properties of vascularised tissue would be extremely beneficial to the study of disease aetiologies and future therapies, including in the case of cancer where there is increasing interest in studying alterations to the microvasculature. Engineered systems can present significant advantages over animal studies, alleviating challenges associated with variable complexity and control. 3D-printable tissue-mimicking hydrogels can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…Since PB concentration plays a fundamental role in hydrogel three-dimensional printing resolution and mechanical properties, its influence on cell characteristics was investigated. Phase contrast microscopy revealed that, similarly to what was observed in previous work [ 12 ], BEMA10 and PEGDA10 do not support HUVEC growth or proliferation. Instead, all GelMA-based formulations supported cell adhesion, growth and proliferation, and the morphology of HUVECs changed depending on the substrate's properties.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Since PB concentration plays a fundamental role in hydrogel three-dimensional printing resolution and mechanical properties, its influence on cell characteristics was investigated. Phase contrast microscopy revealed that, similarly to what was observed in previous work [ 12 ], BEMA10 and PEGDA10 do not support HUVEC growth or proliferation. Instead, all GelMA-based formulations supported cell adhesion, growth and proliferation, and the morphology of HUVECs changed depending on the substrate's properties.…”
Section: Discussionsupporting
confidence: 72%
“…Three-dimensional printing has been investigated extensively to produce tissue-mimicking constructs [ 12 , 13 ]. Continuous advances in three-dimensional printing have led to the development of specialized materials for specific biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%